Periodontal and peri-implant diseases in centenarians - Sekundo, Caroline; Langowski, Eva; Kilian, Samuel; Frese, Cornelia (Journal of clinical periodontology, 2020)
Aims To report the prevalence of periodontal and peri-implant diseases in centenarians in South-Western Germany, examine associations with sociodemographic factors and explore age-related trends. Material and methods Eligible persons born before 1920 were identified from population registries in South-Western Germany. A total of 55 centenarians were visited at home or in nursing care facilities. Of them, 35 were dentate, 33 of which underwent periodontal examination. Implants in 2 edentulous patients were also registered. Results The mean number of teeth was 9.5 ± 7.1; centenarians in need of nursing care had considerably less teeth than others (8.5 versus. 17.0 teeth, p = .03). Mean probing depth was 2.7 ± 0.8mm; mean clinical attachment loss was 4.2 ± 1.7 mm. Severe tooth mobility (degree 2 or 3) and furcation involvement were present in approximately 3% of eligible teeth. According to CDC/AAP classification, 25.8% of centenarians had no or mild periodontitis, 54.8% of centenarians had moderate periodontitis, and only 19.4% were severely affected. Of 27 implants examined in 5 centenarians, 59.3% were classified as healthy, 29.6% had peri-implant mucositis, and 11.1% had peri-implantitis. Conclusions This study reveals the predominance of moderately severe disease in centenarians. While there were high levels of moderate periodontitis and peri-implant mucositis, signs of severe periodontitis, severe furcation involvement, tooth mobility or peri-implantitis were less frequent.
Gesehen am 16.08.2021